Breast Cancer Literacy: Status of Peripheral Health Workers in Lucknow - Ansari, Arshi; Agarwal, Monika; Singh, Vijay Kumar; Nutan, Kumari; Deo, Suajata; Deori, Trideep Jyoti (Asian Pacific Journal of Cancer Care, 2023)
Background: Every woman needs to know the facts, and the fact is, when it comes to breast cancer, every woman is at risk. India accounts for 7.2% of global cancer incidence, but in terms of mortality, the country accounts for 8.3% of global mortality. India faces a high burden of cancer with the late-stage presentation being a common feature. Early detection of cancer is an important strategy for improved survival and simple cost-effective treatment. Low levels of cancer awareness are a significant factor for delay in seeking treatment by women. Objective: The present study was conducted among Peripheral Health Workers (PHWs) in the Lucknow district to assess their perception of risk factors of breast cancer, knowledge of symptoms, early detection methods, and their availability in the district. Methods: The study was conducted from September 2017 to August 2018, among 450 female PHWs working in rural and urban areas of Lucknow. A semi-structured questionnaire was used to collect information about the awareness of PHWs regarding breast cancer. The awareness score was calculated based on their responses. Data were analyzed using SPSS version 24.0 (IBM Corporation). Results: The mean score for overall knowledge of breast cancer was statistically significantly high in BHWs in comparison to ASHAs (Accredited Social Health Activist). The mean knowledge score of signs and symptoms was significantly high among BHWs (Basic Health Workers). PHWs that had undergone training for breast cancer had about 5 times higher chances of having an above-median score. Conclusion: Current low awareness levels, scarcity of resources, and screening programs call for training and refresher pieces of training for peripheral level health workers to empower them to provide preventive health education and screening at the community level. Breastfeeding counseling sessions during home visits and VHNDs could be utilized as an opportunity to create awareness about breast cancer, especially its protective effect on breast cancer.